2015
DOI: 10.1186/s13028-015-0139-6
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging anatomy of the rabbit brain at 3 T

Abstract: BackgroundRabbits are widely accepted as an animal model in neuroscience research. They also represent very popular pet animals, and, in selected clinical cases with neurological signs, magnetic resonance imaging (MRI) may be indicated for imaging the rabbit brain. Literature on the normal MRI anatomy of the rabbit brain and associated structures as well as related reference values is sparse. Therefore, it was the purpose of this study to generate an MRI atlas of the normal rabbit brain including the pituitary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 19 publications
(20 reference statements)
2
18
1
Order By: Relevance
“…The size of the pituitary gland was relatively constant among the 62 rabbits and 66 head CT scans in this study, and the age, weight, or sex of the rabbits did not have a significant impact on pituitary mensuration, confirming our research hypothesis. Our mean CT linear measurements (PG height: 4.22 ± 0.57 mm, PG width: 4.48 ± 0.71 mm, and PG length: 6.02 ± 0.70 mm) were slightly larger than the pituitary mensuration reported on high‐field (3 Tesla) MRI of the brain in five healthy New Zealand white rabbits, 13 with a pituitary gland mean height, width, and length of respectively 3.5, 3.5, and 5.0 mm on the MRI images. These small differences in measurements (≤1.0 mm) may be attributable to variations in the sample population size, user‐dependent variations, and to the difference in image modality.…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…The size of the pituitary gland was relatively constant among the 62 rabbits and 66 head CT scans in this study, and the age, weight, or sex of the rabbits did not have a significant impact on pituitary mensuration, confirming our research hypothesis. Our mean CT linear measurements (PG height: 4.22 ± 0.57 mm, PG width: 4.48 ± 0.71 mm, and PG length: 6.02 ± 0.70 mm) were slightly larger than the pituitary mensuration reported on high‐field (3 Tesla) MRI of the brain in five healthy New Zealand white rabbits, 13 with a pituitary gland mean height, width, and length of respectively 3.5, 3.5, and 5.0 mm on the MRI images. These small differences in measurements (≤1.0 mm) may be attributable to variations in the sample population size, user‐dependent variations, and to the difference in image modality.…”
Section: Discussioncontrasting
confidence: 58%
“…An excellent inter‐ and intraobserver agreement has also been reported in measuring various pituitary gland dimensions on CT images in dogs 8 . Currently, only a few publications detail the normal rabbit head anatomy on CT, 9–11 and only two reports explore the normal rabbit brain on MRI—one on a low‐field (0.2 Telsa) MRI 12 and the other on a high‐field (3 Tesla) MRI 13 . This latter study evaluated the brains of five healthy New Zealand white rabbits on MRI and reported a pituitary gland mean height, width, and length of 3.5, 3.5, and 5.0 mm, respectively 13 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Müllhaupt et al. ), but the young rabbit brain remains incompletely described, and studies were often more specialised in mechanisms than in anatomy (e.g. Allingham et al.…”
Section: Introductionmentioning
confidence: 99%
“…However, the literature concerning the rabbit pup brain anatomy is sparse and most of the studies focus on the adult rabbit. Some brain atlases based on histological sections or fMRI images are available for the adult rabbit (histological: Shek et al 1986;fMRI: Munoz-Moreno et al 2013;M€ ullhaupt et al 2015), but the young rabbit brain remains incompletely described, and studies were often more specialised in mechanisms than in anatomy (e.g. Allingham et al 1998Allingham et al , 1999Jagalska-Majewska et al 2001Charra et al 2012Charra et al , 2013Moreno et al 2013;Schneider et al 2016a,b).…”
Section: Introductionmentioning
confidence: 99%